Analysis of body differences for the design of children's clothing. (December 2018) - Bezerra, G; Carvalho, M; Araujo, A; Rocha, M; Barboza, R
Abstract: This paper discusses anthropometric data obtained through 3D body scanner technology, aiming the dimensioning of Portuguese children´s measurements for the design of clothing. The study comprises boys and girls from the Northern Region of Portugal aged between two and ten years old. The main objective of this part of the study was to evaluate the possibility of grouping children with six and seven years old in a same garment size, proposing the same body measurements in the final standard measurements table. In addition to the children's anthropometric measurements, it was checked the body conformation of the children and the possibility of identifying the main biotypes. As a preliminary result, through cluster analysis it was found that it is possible to combine these children in the same group in the proposed standard measurements table.